The 'population' variable in urban design and regional planning (the case of Greece) - Thomas Papathomas (European Regional Science Association (ERSA), 2010)
The population distribution in the Greek region shows strong spatial disparities. The depopulation of entire areas, coupled with the excessive population growth of the two largest cities (Athens and Thessaloniki) as well as the intense spatial disparities within the cities are significant challenges in managing our country; the main instrument to achieve this management is spatial planning. At the same time, the population is a variable which comprises a deciding factor in the procedure of spatial planning. Exploring the characteristics of the population of a region and predicting the evolution is not an end in itself for analysis, their usefulness, however, lies on the fact that part of the characteristics of urban space is determined by size, demographic and social characteristics of the population concentrated in this space. The purpose of this work is to study how the population variable is included in spatial planning. In order to answer to the above question we will study the technical specifications of the Greek plans trying to understand and specify which characteristics of the population are considered in the design and how. Also, if there are differences between the two main stages of spatial planning (analysis phase, final proposal phase) in relation to the population study. We will study 4 specific cases of randomly chosen masterplans (the corresponding plans of the Greek legislation) in order to try to verify the early feedback which will come up. The conclusions are interesting and highlight some of the weaknesses and shortcomings of the Greek plans and the Greek system of design. Finally, some suggestions are presented which we believe they can improve the current weaknesses.
Keywords: 330